2003
DOI: 10.1007/s00330-003-1885-9
|View full text |Cite
|
Sign up to set email alerts
|

Limitations and pitfalls of Couinaud's segmentation of the liver in transaxial Imaging

Abstract: The segmental anatomy of the human liver has become a matter of increasing interest to the radiologist, especially in view of the need for an accurate preoperative localization of focal hepatic lesions. In this review article first an overview of the different classical concepts for delineating segmental and subsegmental anatomy on US, transaxial CT, and MR images is given. Essentially, these procedures are based on Couinaud's concept of three vertical planes that divide the liver into four segments and of a t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(22 citation statements)
references
References 44 publications
0
22
0
Order By: Relevance
“…This model is a comprehensive topographical concept of functional liver anatomy that is easily interpretable and can be applied in most patients. However, an increasing body of evidence suggests that this concept may be an oversimplification [27][28][29][30][31]. Anatomical and radiological investigations have confirmed that the segmental boundaries, as indicated by the hepatic veins and the level of the right portal trunk, do Aberrant left and right hepatic arteries not consistently coincide with the exact location of the true portal scissurae in individual patients [28,29,31].…”
Section: Aberrant Left Hepatic Arteriesmentioning
confidence: 99%
“…This model is a comprehensive topographical concept of functional liver anatomy that is easily interpretable and can be applied in most patients. However, an increasing body of evidence suggests that this concept may be an oversimplification [27][28][29][30][31]. Anatomical and radiological investigations have confirmed that the segmental boundaries, as indicated by the hepatic veins and the level of the right portal trunk, do Aberrant left and right hepatic arteries not consistently coincide with the exact location of the true portal scissurae in individual patients [28,29,31].…”
Section: Aberrant Left Hepatic Arteriesmentioning
confidence: 99%
“…The following measurements of the liver were performed independently by readers (1). Midhepatic point craniocaudad (MHP CC); (2). Maximum CC to liver tip (Max CC); (3).…”
Section: Linear Hepatic Measurementsmentioning
confidence: 99%
“…Estimation of liver size can be used as an index to monitor various aspects of liver disease and response to treatment [1,2] Serial magnetic resonance imaging (MRI) may be used to monitor patient treatment and determine management [3]. Midclavicular (MCL), craniocaudad (CC), or midhepatic (MHP) CC measurements have been used in ultrasound (US) to estimate liver size [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…However, they are unlikely to demonstrate internal vessels and external structures of liver together. Meanwhile, it is also well known that some hepatic segments, described by Couinaud, have no visible anatomical landmarks corresponding with them on the liver surface (Strunk et al, 2003). Therefore, it is very necessary to prepare new specimens displaying both the intrahepatic vessels and external structures simultaneously.…”
Section: Significance Of Preparing Casting and Transparent Liver Specmentioning
confidence: 99%